1994
DOI: 10.1021/jo00102a019
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of Alkoxy Radicals and Oxidative Elimination of Alicyclic Iodides

Abstract: The azaallyl cation-mediated [4 + 3] cycloaddition with spiro[2.4]hepta-4,6-diene by the procedure of Schmid provides the tricyclic cycloadducts of general type 3. The keto bridge of the cycloadducts 17c, 21, and 22 has been cleaved by PhI(OAc)2-l2 (Suárez cleavage), which involves ^-fragmentation of an alkoxy radical, to furnish iodo lactones 19,32, and 30a,b, respectively. Subsequent oxidation of these alkyl iodides has been investigated to develop a new synthetic route for bridgehead olefins (i.e., 33) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Alkylation of methyl α-phenylsulfonylacetate with this tosylate then led to 30 as a mixture of diastereomers in 53% yield based on alcohol 28 . Using the halogenation conditions described by Cha et al,14 enol ether 30 was transformed to α-chloroketone 31 with N -chlorosuccinimide in 64% yield. Conversion of this α-chloroketone to O -TBS-oxime 32 , followed by cyclization under the usual conditions afforded the bicyclo[3.2.1]octane 33a as a single diastereomer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alkylation of methyl α-phenylsulfonylacetate with this tosylate then led to 30 as a mixture of diastereomers in 53% yield based on alcohol 28 . Using the halogenation conditions described by Cha et al,14 enol ether 30 was transformed to α-chloroketone 31 with N -chlorosuccinimide in 64% yield. Conversion of this α-chloroketone to O -TBS-oxime 32 , followed by cyclization under the usual conditions afforded the bicyclo[3.2.1]octane 33a as a single diastereomer.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the mixture was reduced to the corresponding amine 35 ,16 followed by treatment of the crude material with tosyl chloride to afford sulfonamide 36 which could be purified by chromatography. We were pleased to find that under the Cha reaction conditions,14 enol ether 36 was cleanly transformed to α-chloroketone 37 in high yield. It should be added that we have observed that halogenation of some vinyl chloride systems related to enol ether 36 using our sodium hypochlorite method led to significantly lower yields of the respective α-chloroketones, and also produced varying amounts of products resulting from N -chlorination of the sulfonamide 17…”
Section: Resultsmentioning
confidence: 99%
“…[23] We isolated only the 5-methylenefuran-2(5H)-one 16, probably by elimination of the corresponding iodoso intermediate 15. [24] Scheme 4. Reagents and conditions: (a) NCS, K 2 CO 3 , CH 2 To avoid this side reaction, this process was tested with the reduced lactone 17 (Scheme 5).…”
Section: Resultsmentioning
confidence: 99%
“…[22] Allylic bromination of 18 with N-bromosuccinimide and 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) gave 7abromo derivative 19 in 50 %y ield, together with as mall amount of a7,11-dibrominated product. [26] Finally, removal of the two protecting groups at the C3 and C7 positions in one pot completed the synthesis of 1,w hich showed good agreement with natural strophasterol Ainterms of NMR spectrum, melting point, and specific rotation. [25] Dehydrobromination of 19 to diene 20 was first attempted by treating it with DBUi nT HF,b ut the product obtained was ar oughly 1:4m ixture of 20 and undesired D 7,9(11) -diene 20' '.T his problem could be circumvented by prior conversion of 19 into aselenide intermediate and subsequent oxidative elimination in one pot, furnishing 20 in 74 %yield, which set the stage for the installation of the epoxy alcohol unit on the B-ring.…”
Section: Angewandte Chemiementioning
confidence: 99%